Non-financial reports, anti-corruption performance and corporate reputation - Aldaz, Maider; Alvarez, Igor; Calvo, José Antonio (Review of Business Management, 2015)
Objective – This paper analyzes whether the anti-corruption reporting practices of the companies are a reflection of adequate anti-corruption systems put in place by companies, or whether the disclosure is merely a tool for companies to improve their reputation and thus maintain their legitimacy. Design/methodology/approach – We apply the PLS method to the collected data in a content analysis of the sustainability reports of 31 companies within the Ibex 35 in December 2008. Theoretical foundation – In the analysis, we use both the legitimacy theory and the stakeholder theory, because we consider them as complementary theories and consistent with our approach. Findings – The results show that regarding the corruption issue there is a negative relationship between disclosure and performance, that is, companies with poor performance disclose more. On the other hand, the results reflect the existence of a positive relationship between disclosure and reputation, i.e. report information to interested parties enhances the perception of stakeholders about the company. This finding could be justified by the above two theories. However, we can’t conclude that companies with good performance disclose information to key stakeholders in order to strengthen relations, as stated by the stakeholder theory. Practical implications – this study provides evidence of how companies use non-financial reporting-specifically anti-corruption data- to improve corporate reputation. It is also noted that reporting practices not necessarily have to be in accordance with the actual anti-corruption practices of firms.